Characterization of Workloads in Studies on Virtual Memory Management - Cassettari, Hugo Henrique; Midorikawa, Edson Toshimi (Proceedings of the Workshop on Performance of Computer and Communication Systems (WPerformance), 2004)
The characterization of workloads for memory systems evaluation is important because it allows to detect factors in programs which may or may not favor the performance of each possible system configuration. This paper describes the Elephantools: a software tools package applied to the characterization of workloads used in experiments on virtual memory management. Providing visual and statistics resources for identifying memory access patterns inherent in specific programs, the Elephantools contributes both to the enrichment of studies on reference locality and to the understanding of some phenomena observed in simulations.